2021
DOI: 10.21511/bbs.16(4).2021.08
|View full text |Cite
|
Sign up to set email alerts
|

Bank solvency: The role of credit and liquidity risks, regulatory capital and economic stability

Abstract: Banking stability is essential to any economy due to its many functions, including intermediation, payment facilitation, and credit creation. Thus, the stability of the banking industry is one of the critical ingredients in economic growth. This paper analyzes how bank capital requirements, credit, and liquidity impact bank solvency using ten major banks that control 90% of the market share in the UK in 2009–2018. The GMM model indicates a strong association between credit and liquidity risks. That is, when ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Profit level has a positive and significant influence on bank risk-taking when the latter is measured by the risk assets-to-total assets ratio, but the relationship turned negative when bank risk is measured by non-performing loans ratios in Delis and Kouretas (2011) . Likewise, in a recent study, ROE is reported as positive in impacting bank insolvency ( Oino, 2021 ).…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 73%
See 1 more Smart Citation
“…Profit level has a positive and significant influence on bank risk-taking when the latter is measured by the risk assets-to-total assets ratio, but the relationship turned negative when bank risk is measured by non-performing loans ratios in Delis and Kouretas (2011) . Likewise, in a recent study, ROE is reported as positive in impacting bank insolvency ( Oino, 2021 ).…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 73%
“…It is used extensively in measuring bank default, for instance in Ghenimi et al. (2017) , Salami (2018) , Di Tommaso and Thornton (2020) , Oino (2021) , among others.…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
“…So as a major part of policy making of a country, the importance of ensuring solvency in banks is out of denial. It is extensively outlined in literature with high media coverage that bank insolvency creates economic vulnerabilities by backsliding foreign investments, rising capital short-fall, and dipping the major industries into crises (Oino 2021). The fall of the industries eventually creates high level of unemployment and inflation in the economy.…”
mentioning
confidence: 99%